Border Thinking in the Training of Imams and Muslim Caregivers - Schmid, Hansjörg (International journal of practical theology, 2025)
The continuing education of imams and Muslim caregivers in Europe, which complements their basic training, has so far mostly been analysed within social and political debates. Continuing education is understood as a contact zone where multiple perspectives and bodies of knowledge meet, where border thinking emerges and leads to the development of creative strategies for dealing with this diversity. In this article, we will focus on the active role imams and caregivers have in such programmes. Our case study example shows how imams and caregivers reconcile binary preconceptions and strive for innovative perspectives on Islam and society, resulting in transformative ideas which are not only useful for the continuing education of these target groups, but also for an emerging Islamic practical theology.